THE IMPLEMENTATION OF DIGITALIZATION ON EMPLOYEE PERFORMANCE MODERATED BY EMPLOYEE ENGAGEMENT AT THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE - Yusuf T. Lubis (RADJA PUBLIKA, 2025)
This study aims to determine the effect of digitalization implementation on employee performance moderated by employee engagement in the General Bureau of the Regional Secretariat of North Sumatra Province (Setdaprovsu). The North Sumatra Provincial Government, particularly in the General Bureau of the Setdaprovsu, has begun implementing a digital-based work system. This is done to be in line with the central government and other provinces that have already used digital technology. Digitalization is expected to make work faster, more efficient, and improve employee performance. However, some older employees find it difficult to use modern technology. A lack of understanding of digital systems makes it difficult for them to adapt. Therefore, it is important to determine whether the implementation of digitalization truly has an impact on employee performance, and whether employee engagement in their work can help in facing this challenge. This research method uses a quantitative approach by distributing questionnaires to 76 employees of the General Bureau of the Setdaprovsu as respondents online using Google-form. Then the data obtained will be converted into numbers with a Likert Scale which aims to find the effect of the independent variables on the dependent variable and intervening variables, then processed using the Smart-PLS (Partial Least Squares) Statistics application. Based on the analysis, it can be concluded that the implementation of digitalization has a positive impact on employee performance. This indicates that the higher the level of digital technology utilization in the workplace, the greater the effectiveness and efficiency of employee performance. Furthermore, employee engagement has been shown to positively moderate the relationship between digitalization and employee performance. Therefore, the influence of digitalization on performance will be stronger if employees are highly engaged with their work.